Preparation method of modified positive electrode material, product of modified positive electrode material and application of modified positive electrode material in metal ion battery
By mixing organic acid with the positive electrode material, alkaline impurities on the surface of the positive electrode material are removed and active metal compensator is formed, which solves the problem of residual alkali on the surface of the positive electrode material and improves the electrochemical performance and cycle stability of the battery.
Patent Information
- Application Number
- CN202411384235.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the synthesis, treatment and storage of existing positive electrode materials, alkaline impurities often remain on the surface, affecting the electrochemical reaction, leading to metal ions loss and reducing battery performance.
The organic acid is mixed with the positive electrode material for metal ion batteries, and a solvent is added at room temperature and stirred to form a slurry. After drying, the inert residual alkali on the surface of the positive electrode material is removed to form an active metal compensator.
Effectively remove residual alkali on the surface of the positive electrode material, avoid metal ions loss, improve the electrochemical performance and cycle stability of the battery, reduce production energy consumption, and is suitable for large-scale production.
Smart Images

Figure CN119447281A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of positive electrode materials for metal ion batteries, and relates to a preparation method of a modified positive electrode material and a product thereof and application of the modified positive electrode material in metal ion batteries. Background Art
[0002] Metal-ion batteries (such as lithium / sodium / potassium-ion batteries), as core technology components at the forefront of modern energy storage technology, are driving the transformation from personal electronic products to electric vehicles and even large-scale energy storage systems. Studies have shown that the performance of metal-ion batteries is highly dependent on the quality and characteristics of the positive electrode materials, especially the surface state of the positive electrode materials, which directly affects the electrochemical behavior, long-cycle stability and safety of the battery. However, during the synthesis, processing and storage of positive electrode materials, alkaline impurities are often left on their surface. These residual alkalis not only occupy active sites and affect electrochemical reactions, but also cause metal ion loss, seriously affecting battery performance.
[0003] At present, in order to improve the situation of residual alkali on the surface of positive electrode materials, strong acid immersion method and high temperature calcination method can be used. Among them, although the strong acid immersion method can effectively remove the alkaline substances on the surface of the positive electrode material, the strong acidic conditions are often excessive. It may not only corrode the basic structure of the positive electrode material and cause the loss of active substances, but also cause the uncontrollable loss of lithium, sodium and potassium metal ions, thereby reducing the electrochemical performance and cycle stability of the battery. Although the high temperature calcination method can use high temperature to cause the volatilization of alkaline substances on the surface of the positive electrode material, high temperature treatment also faces problems such as material structure destruction, high energy consumption and complex process, and it is difficult to accurately control the state of metal ions, which can easily cause waste of resources and environmental pollution. Therefore, how to modify the positive electrode material and effectively remove the residual alkali on the surface of the positive electrode material has become one of the key technical challenges to improve the comprehensive performance of the battery. Summary of the invention
[0004] In view of this, one of the objects of the present invention is to provide a method for preparing a modified positive electrode material; a second object of the present invention is to provide a modified positive electrode material; a third object of the present invention is to provide an application of the modified positive electrode material in the preparation of metal ion batteries.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] 1. A method for preparing a modified positive electrode material, the preparation method being as follows: mixing an organic acid with a positive electrode material for a metal ion battery, then adding a solvent at room temperature, and then stirring at 10 to 80° C. for 0.5 to 5 hours to form a slurry, and drying the slurry to obtain the modified positive electrode material;
[0007] The organic acid is any one or more of iminodiacetic acid, methyliminodiacetic acid, N-(2-carboxyethyl)iminodiacetic acid, iminodisuccinic acid, nitrilotriacetic acid, thiodiacetic acid or thiodiacetic acid;
[0008] The solvent is any one or more of deionized water, ethanol, acetone, acetonitrile, butanone, cyclohexanone, dichloromethane or N-methylpyrrolidone.
[0009] Preferably, the positive electrode material for a metal ion battery is any one of a positive electrode material for a lithium ion battery, a positive electrode material for a sodium ion battery or a positive electrode material for a potassium ion battery.
[0010] Preferably, the positive electrode material for the lithium ion battery is any one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide or lithium cobalt oxide; the positive electrode material for the sodium ion battery is any one or more of sodium iron pyrophosphate, sodium manganese pyrophosphate, sodium manganese iron pyrophosphate, sodium iron pyrophosphate phosphate, sodium manganese pyrophosphate phosphate, sodium manganese iron pyrophosphate phosphate, sodium nickel manganese titanate or sodium nickel manganese ferrate; the positive electrode material for the potassium ion battery is any one or more of potassium iron pyrophosphate, potassium nickel manganese titanate or potassium nickel manganese ferrate.
[0011] Further preferably, the positive electrode material for the lithium ion battery is lithium nickel cobalt manganese oxide; the positive electrode material for the sodium ion battery is sodium iron pyrophosphate; and the positive electrode material for the potassium ion battery is potassium nickel manganese titanate.
[0012] Preferably, the organic acid is any one or both of iminodiacetic acid and nitrilotriacetic acid.
[0013] Preferably, the solvent is N-methylpyrrolidone.
[0014] Preferably, the mass ratio of the organic acid, the positive electrode material for metal ion batteries and the solvent is 1:1:2.5 to 1:100:250.
[0015] Preferably, the drying temperature is 40 to 150° C. and the drying time is 2 to 24 hours.
[0016] More preferably, the drying temperature is 80-120° C. and the drying time is 5-15 hours.
[0017] 2. The modified positive electrode material prepared according to the preparation method.
[0018] 3. Application of the modified positive electrode material in the preparation of metal ion batteries.
[0019] The beneficial effects of the present invention are as follows: the present invention provides a method for preparing a modified positive electrode material, a product thereof, and an application thereof in a metal ion battery. By selecting an organic acid with low corrosivity and low cost, and utilizing a mild acid-base neutralization reaction to convert the inert residual alkali on the surface of the positive electrode material for a metal ion battery into an active residual alkali, the problem of removing the residual alkali on the surface of the positive electrode material without destroying the microstructure of the positive electrode material is solved, and the loss of alkali metal ions in the residual alkali is effectively avoided, that is, the metal compensator is formed in situ, and the pre-metallization effect is achieved. By adjusting different electron-donating groups on the main chain of the organic acid to achieve the control of the capacity and voltage of the metal compensator, the derived metal compensator has strong electrochemical activity, low decomposition potential, high capacity and first-cycle utilization rate. In addition, the method does not require high-temperature sintering or strong acid treatment, can significantly reduce production energy consumption, shorten the production cycle, improve production efficiency, have low environmental requirements, and is suitable for large-scale production and application. The modified positive electrode material prepared based on the method is applied to metal ion batteries, which solves the problem of the loss of the battery's first charge and discharge capacity and effectively improves the battery's energy density.
[0020] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:
[0022] Figure 1 These are scanning electron microscope images of the positive electrode material of sodium nickel manganese titanate and sodium nickel manganese titanate modified with iminodiacetic acid in Example 3, wherein (a) is a scanning electron microscope image of sodium nickel manganese titanate, and (b) is a scanning electron microscope image of the positive electrode material of sodium nickel manganese titanate modified with iminodiacetic acid;
[0023] Figure 2 The X-ray powder diffraction patterns of the positive electrode materials of sodium nickel manganese titanate and sodium nickel manganese titanate modified with iminodiacetic acid in Example 3, wherein (a) is the X-ray powder diffraction pattern of sodium nickel manganese titanate, and (b) is the X-ray powder diffraction pattern of the positive electrode material after sodium nickel manganese titanate is modified with iminodiacetic acid;
[0024] Figure 3 The infrared spectra of iminodiacetic acid, sodium nickel manganese titanate, the positive electrode material after sodium nickel manganese titanate is modified by iminodiacetic acid (sodium nickel manganese titanate @ iminodiacetic acid), and disodium iminodiacetic acid generated by the reaction of iminodiacetic acid and residual alkali on the surface of sodium nickel manganese titanate in Example 3;
[0025] Figure 4 These are scanning electron micrographs of the positive electrode material of sodium ferric pyrophosphate and sodium ferric pyrophosphate modified with iminodiacetic acid in Example 4, wherein (a) is a scanning electron micrograph of sodium ferric pyrophosphate, and (b) is a scanning electron micrograph of the positive electrode material of sodium ferric pyrophosphate modified with iminodiacetic acid;
[0026] Figure 5 The first cycle voltage-specific capacity curve of the metal ion battery assembled based on the modified positive electrode material in Example 3 and the slurry material based on the sodium nickel manganese titanate not modified by any organic acid in Comparative Example 1;
[0027] Figure 6 The first cycle voltage-specific capacity curve of the metal ion battery assembled based on the modified positive electrode material in Example 4 and the slurry material based on the sodium iron pyrophosphate not modified by any organic acid in Comparative Example 2;
[0028] Figure 7 The first cycle voltage-specific capacity curve of the metal ion battery assembled based on the modified positive electrode material in Example 5 and the slurry material based on the sodium iron pyrophosphate not modified by any organic acid in Comparative Example 2;
[0029] Figure 8 It is a first cycle voltage-specific capacity curve of a metal ion battery assembled based on the modified positive electrode material in Example 6 and the slurry material based on the sodium iron pyrophosphate not modified by any organic acid in Comparative Example 2. DETAILED DESCRIPTION
[0030] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.
[0031] Example 1
[0032] Preparation of positive electrode materials after lithium nickel cobalt manganese oxide modified by iminodiacetic acid
[0033] Mix 0.04 g of iminodiacetic acid with 0.5 g of lithium nickel cobalt manganese oxide, then add 20 mL of ethanol at 25° C., followed by mechanical stirring at 25° C. for 1 hour to form a slurry, and place the resulting slurry in a drying oven at 80° C. and dry for 15 hours to obtain a modified positive electrode material.
[0034] Example 2
[0035] Preparation of positive electrode materials after lithium manganate modified by methyliminodiacetic acid
[0036] 0.1 g of methyliminodiacetic acid was mixed with 1.5 g of lithium manganate, and then 40 mL of acetonitrile was added at 25° C., followed by mechanical stirring at 35° C. for 2.5 h to form a slurry. The resulting slurry was placed in a drying oven at 100° C. and dried for 15 h to obtain a modified positive electrode material.
[0037] Example 3
[0038] Preparation of positive electrode material after sodium nickel manganese titanate modified by iminodiacetic acid
[0039] 0.06 g of iminodiacetic acid was mixed with 0.8 g of sodium nickel manganese titanate, and then 30 mL of N-methylpyrrolidone was added at 25° C., followed by mechanical stirring at 30° C. for 2 h to form a slurry. The resulting slurry was placed in a drying oven at 120° C. and dried for 10 h to obtain a modified positive electrode material.
[0040] The positive electrode materials of sodium nickel manganese titanate and sodium nickel manganese titanate modified with iminodiacetic acid in Example 3 were tested by scanning electron microscope. The experimental results are as follows: Figure 1 (a) and Figure 1 Compared with sodium nickel manganese titanate, the surface morphology of the positive electrode material after sodium nickel manganese titanate modified by iminodiacetic acid is basically unchanged. This is because a mild acid-base neutralization reaction occurs between the residual alkali on the surface of sodium nickel manganese titanate and iminodiacetic acid. X-ray powder diffraction tests were performed on the sodium nickel manganese titanate and the positive electrode material after sodium nickel manganese titanate modified by iminodiacetic acid in Example 3. The experimental results are as follows: Figure 2 (a) and Figure 2 As shown in (b). By comparison, it can be seen that the physical phase of the positive electrode material does not change after being modified by iminodiacetic acid. In Example 3, iminodiacetic acid, sodium nickel manganese titanate, the positive electrode material after sodium nickel manganese titanate modified by iminodiacetic acid (sodium nickel manganese titanate @ iminodiacetic acid), and disodium iminodiacetic acid generated by the reaction of iminodiacetic acid and residual alkali on the surface of sodium nickel manganese titanate were tested by infrared spectroscopy. The experimental results are shown in Figure 2. Figure 3 As shown. Figure 3 It can be seen that iminodiacetic acid and disodium iminodiacetate are located at 3089 cm -1 and 1703cm -1 The peaks at 1 and 2 disappear, and these two peaks can be attributed to OH - Compared with sodium nickel manganese titanate, the positive electrode material modified with iminodiacetic acid has an additional 1607 cm -1Peak at 1607(1578)cm -1 The peak at belongs to the NH bond, which proves that the positive electrode material after sodium nickel manganese titanate modified by iminodiacetic acid generates a metal compensator.
[0041] Example 4
[0042] Preparation of positive electrode materials after sodium iron pyrophosphate modified by iminodiacetic acid
[0043] 0.06 g of iminodiacetic acid was mixed with 1 g of sodium ferric pyrophosphate, and then 30 mL of N-methylpyrrolidone was added at 25° C., followed by mechanical stirring at 20° C. for 2 h to form a slurry. The resulting slurry was placed in a drying oven at 120° C. and dried for 10 h to obtain a modified positive electrode material.
[0044] The positive electrode materials of sodium iron pyrophosphate and sodium iron pyrophosphate modified by iminodiacetic acid in Example 4 were tested by scanning electron microscope. The experimental results are as follows: Figure 4 (a) and Figure 4 As shown in (b), the surface morphology of the cathode material before and after modification is basically unchanged due to the mild acid-base neutralization reaction between the residual alkali on the surface of sodium ferric pyrophosphate and iminodiacetic acid.
[0045] Example 5
[0046] The difference from Example 4 is that 0.06 g of iminodiacetic acid is replaced by 0.08 g of iminodiacetic acid, and the other conditions remain unchanged.
[0047] Example 6
[0048] The difference from Example 4 is that 0.06 g of iminodiacetic acid is replaced by 0.12 g of iminodiacetic acid, and the other conditions remain unchanged.
[0049] Example 7
[0050] Preparation of positive electrode materials after sodium iron phosphate pyrophosphate modified by iminodiacetic acid
[0051] 0.06 g of iminodiacetic acid was mixed with 1.2 g of sodium ferric phosphate pyrophosphate, and then 40 mL of N-methylpyrrolidone was added at 25° C., followed by mechanical stirring at 40° C. for 2 h to form a slurry, and the resulting slurry was placed in a drying oven at 120° C. and dried for 10 h to obtain a modified positive electrode material.
[0052] Example 8
[0053] Preparation of positive electrode material after modification of potassium nickel manganese ferrite with nitrilotriacetic acid
[0054] 0.06 g of nitrilotriacetic acid was mixed with 0.5 g of potassium nickel manganese ferrite, and then 40 mL of N-methylpyrrolidone was added at 25° C., followed by mechanical stirring at 45° C. for 2 h to form a slurry. The resulting slurry was placed in a drying oven at 120° C. and dried for 10 h to obtain a modified positive electrode material.
[0055] Example 9
[0056] Preparation of positive electrode material after potassium nickel manganese ferrite modified by iminodisuccinic acid
[0057] Mix 0.06 g of iminodisuccinic acid with 0.5 g of potassium nickel manganese ferrite, then add 40 mL of N-methylpyrrolidone at 25° C., followed by mechanical stirring at 50° C. for 2 h to form a slurry, and place the resulting slurry in a drying oven at 120° C. for 10 h to obtain a modified positive electrode material.
[0058] Example 10
[0059] Preparation of positive electrode material after modification of potassium nickel manganese ferrite with methyliminodiacetic acid
[0060] 0.06 g of methyliminodiacetic acid was mixed with 0.5 g of potassium nickel manganese ferrite, and then 40 mL of N-methylpyrrolidone was added at 25° C., followed by mechanical stirring at 40° C. for 2 h to form a slurry. The resulting slurry was placed in a drying oven at 120° C. and dried for 10 h to obtain a modified positive electrode material.
[0061] Similarly, the positive electrode materials for metal ion batteries and the positive electrode materials modified with organic acids in the other embodiments above were subjected to scanning electron microscopy, X-ray powder diffraction and infrared spectroscopy tests, respectively, and similar experimental results as those in Examples 3 and 4 were obtained. That is, the introduction of a small amount of organic acid does not lead to changes in the surface morphology and phase structure of the positive electrode material before and after modification.
[0062] Comparative Example 1
[0063] Preparation of slurry material of sodium nickel manganese titanate without any organic acid modification
[0064] 30 mL of N-methylpyrrolidone was added to 0.8 g of sodium nickel manganese titanate at 25° C., and then mechanically stirred at 25° C. for 2 h to form a slurry. The resulting slurry was placed in a drying oven at 120° C. and dried for 10 h to obtain a slurry material of sodium nickel manganese titanate that was not modified by any organic acid.
[0065] Comparative Example 2
[0066] Preparation of slurry material of sodium ferric pyrophosphate without any organic acid modification
[0067] 30 mL of N-methylpyrrolidone was added to 1 g of sodium iron pyrophosphate at 25° C., and then mechanically stirred at 30° C. for 2 h to form a slurry. The resulting slurry was placed in a drying oven at 120° C. and dried for 10 h to obtain a slurry material of sodium iron pyrophosphate that was not modified by any organic acid.
[0068] Comparative Example 3
[0069] Preparation of slurry material of lithium nickel cobalt manganese oxide without any organic acid modification
[0070] 30 mL of N-methylpyrrolidone was added to 1 g of lithium nickel cobalt manganese oxide at 25° C., and then mechanically stirred at 45° C. for 2 h to form a slurry. The resulting slurry was placed in a drying oven at 120° C. and dried for 10 h to obtain a slurry material of lithium nickel cobalt manganese oxide that was not modified by any organic acid.
[0071] Comparative Example 4
[0072] Preparation of slurry material of potassium nickel manganese ferrite without any organic acid modification
[0073] 30 mL of N-methylpyrrolidone was added to 1 g of potassium nickel manganese ferrite at 25° C., and then mechanically stirred at 35° C. for 2 h to form a slurry. The resulting slurry was placed in a drying oven at 120° C. for 10 h to obtain a slurry material of potassium nickel manganese ferrite that was not modified by any organic acid.
[0074] The modified positive electrode materials in Examples 1 to 10, the slurry material of sodium nickel manganese titanate without any organic acid modification in Comparative Example 1, the slurry material of sodium ferric pyrophosphate without any organic acid modification in Comparative Example 2, the slurry material of lithium nickel cobalt manganese oxide without any organic acid modification in Comparative Example 3, and the slurry material of potassium nickel manganese ferrite without any organic acid modification in Comparative Example 4 were mixed with a carbon black conductive additive and a polyvinylidene fluoride binder in a mass ratio of 7:2:1 to prepare a positive electrode, and the corresponding metal lithium sheet, metal sodium sheet and metal potassium sheet were used as negative electrodes, glass fiber was used as a separator, and the corresponding 1 mol / L LiPF 6 、NaClO 4 and KClO 4 The ester solution is the electrolyte (the electrolyte is specifically LiPF 6 、NaClO 4 or KClO 4As the solute, ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1 were supplemented with 5 vol.% of fluoroethylene carbonate (FEC) additive as the solvent), and then the corresponding metal ion button batteries were assembled in a nitrogen-filled glove box, and then the electrochemical performance of each metal ion button battery was tested under the conditions of a voltage window of 1.5 to 4.3 V and a current density of 50 mA / g, as shown in Table 1.
[0075] Table 1 Electrochemical performance of metal ion batteries assembled based on the materials prepared in Examples 1 to 10 and Comparative Examples 1 to 4
[0076] Battery ID First cycle charging capacity (mAh / g) Capacity retention rate after 100 cycles (%) Example 1 154.6 93.3% Example 2 136.4 90.28% Example 3 131.7 93.93% Example 4 114.9 96.72% Example 5 108.1 95.05% Example 6 102.8 98.87% Example 7 109.2 96.93% Example 8 124.6 90.72% Example 9 138.4 91.75% Example 10 136.4 90.28% Comparative Example 1 120.8 86.68% Comparative Example 2 88.3 93.28% Comparative Example 3 98.2 91.2% Comparative Example 4 118.2 90.1%
[0077] Among them, the first cycle voltage-specific capacity curve of the metal ion battery assembled based on the materials in Example 3, Example 4, Example 5, Example 6, Comparative Example 1 and Comparative Example 2 is selected and plotted, such as Figure 5 , Figure 6 , Figure 7 and Figure 8 As shown. Figures 5 to 8It can be seen that the inert residual alkali on the surface of the unmodified positive electrode material in the embodiment is converted into an active metal compensator after a mild acid-base reaction with an organic acid, and its decomposition voltage is between 3.8 and 4.3V, which is lower than the upper limit voltage of the positive electrode material. In addition, by comparing the first-cycle charging capacity of Examples 1 to 10 with Comparative Examples 1 to 4, it is proved that the obtained metal compensator has a feasible metal compensation effect. For example, the first-cycle charging capacity of the metal ion battery assembled based on the material prepared in Comparative Example 1 is 120.8mAh / g, and the capacity retention rate after 100 cycles is 86.68%. When 13% of iminodiacetic acid (corresponding to Example 3) is added, the first-cycle charging capacity of the battery reaches 131.7mAh / g, and the capacity retention rate after 100 cycles is 93.93%. The first cycle charging capacity of the metal ion battery assembled based on the material prepared in Comparative Example 2 is 88.3 mAh / g, and the capacity retention rate after 100 cycles is 93.28%. When 8% of iminodiacetic acid (corresponding to Example 5) is added, the first cycle charging capacity of the battery reaches 108.1 mAh / g, and the capacity retention rate after 100 cycles is 95.05%. Similarly, by comparing the charging capacity and capacity retention rate in Examples 1 to 2 and Comparative Example 3 and Examples 8 to 10 and Comparative Example 4, it can be found that the metal compensator obtained by the present invention has a practical metal compensation effect on sodium ion batteries, as well as lithium ion batteries and potassium ion batteries. The compensation of sodium, lithium and potassium can effectively solve the irreversible sodium, lithium and potassium losses during the formation of SEI, thereby improving the electrochemical performance of sodium, lithium and potassium ion batteries. The above experimental results also show that the layered, polyanionic positive electrode materials obtained after organic acid modification of sodium, lithium and potassium salts show good capacity retention in long-term cycle tests, proving the effectiveness of acid treatment.
[0078] In summary, the present invention provides a method for preparing a modified positive electrode material, a product thereof, and an application thereof in a metal ion battery. The modified positive electrode material is achieved by removing the inert residual alkali on the surface of the positive electrode material for a metal ion battery by an organic acid. The method not only solves the problem of residual alkali on the surface of the positive electrode material, but also can compensate for metal in situ, thereby effectively solving the irreversible loss of metal ions during the formation of SEI, thereby improving the electrochemical properties of the battery.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a modified positive electrode material, characterized in that: The preparation method is as follows: an organic acid is mixed with a positive electrode material for a metal ion battery, a solvent is added at room temperature, and then stirred at 10 to 80° C. for 0.5 to 5 hours to form a slurry, and the slurry is dried to obtain a modified positive electrode material; The organic acid is any one or more of iminodiacetic acid, methyliminodiacetic acid, N-(2-carboxyethyl)iminodiacetic acid, iminodisuccinic acid, nitrilotriacetic acid, thiodiacetic acid or thiodiacetic acid; The solvent is any one or more of deionized water, ethanol, acetone, acetonitrile, butanone, cyclohexanone, dichloromethane or N-methylpyrrolidone.
2. The preparation method according to claim 1, characterized in that: The positive electrode material for a metal ion battery is any one of a positive electrode material for a lithium ion battery, a positive electrode material for a sodium ion battery, and a positive electrode material for a potassium ion battery.
3. The preparation method according to claim 2, characterized in that: The positive electrode material for the lithium ion battery is any one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide or lithium cobalt oxide; the positive electrode material for the sodium ion battery is any one or more of sodium iron pyrophosphate, sodium manganese pyrophosphate, sodium manganese iron pyrophosphate, sodium iron pyrophosphate phosphate, sodium manganese pyrophosphate phosphate, sodium manganese iron pyrophosphate phosphate, sodium nickel manganese titanate or sodium nickel manganese ferrate; the positive electrode material for the potassium ion battery is any one or more of potassium iron pyrophosphate, potassium nickel manganese titanate or potassium nickel manganese ferrate.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the organic acid, the positive electrode material for metal ion batteries and the solvent is 1:1:2.5 to 1:100:
250.
5. The preparation method according to claim 1, characterized in that: The drying temperature is 40 to 150° C. and the drying time is 2 to 24 hours.
6. The modified positive electrode material prepared according to the preparation method according to any one of claims 1 to 5.
7. Use of the modified positive electrode material according to claim 6 in the preparation of metal ion batteries.
Citation Information
Patent Citations
Modification method of high-nickel oxide, positive electrode material and lithium ion battery
CN115863585A
Composite lithium-rich material and preparation method thereof, positive pole piece and secondary battery
CN117855439A
Low-residual alkali sodium ion positive electrode material and modification method thereof
CN117976839A
Layered oxide positive electrode material with low surface residual alkali and preparation method and application thereof
CN118231636A
Cited By
Preparation and application of hydrophobically modified sodium electrode layered oxide
CN122136343A